The Influence Of The Campus Environment On Students Learning Motivation - Anggun Paulina Manik; Mawar Lestari Hutagaol; Yuliana Sari Angkat; Asmin (Outline Publisher, 2026)
This study aims to determine the influence of the campus environment on student learning motivation. A conducive campus environment is believed to play an important role in encouraging students' enthusiasm, interest, and desire to learn optimally. This study used a quantitative approach with a survey method involving a number of respondents from various study programs. Data were collected through a questionnaire covering aspects of environmental cleanliness, comfort of facilities, academic atmosphere, and social relationships on campus. The results of the study indicate that the campus environment has a positive and significant influence on student learning motivation. The better the condition and atmosphere of the campus, the higher the level of learning motivation of students. This finding emphasizes the important role of educational institutions in creating a comfortable, safe, and supportive learning environment for academic activities.